FORMATION OF ABBREVIATIONS IN MEDICAL TERMINOLOGY IN UZBEK LANGUAGE (Центральноазиатский журнал образования и инноваций, 2024)
This article covers medical terminology and its integration relations with linguistics. Pleonastic units formed when medical terms occur in speech are analyzed. Also, the features of the formation of medical terms are classified.